2002
DOI: 10.1053/jlts.2002.32943
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in the liver graft monitored continuously with microdialysis during liver transplantation in a pig model

Abstract: Microdialysis provides the opportunity to continuously monitor metabolic changes in tissue. The aim of the study is to monitor metabolic changes in the liver graft over time during transplantation in a pig model. Fourteen littermate female pigs with a body weight of 30 to 34 kg were used for seven orthotopic liver transplantations. Intrahepatic implantation of a microdialysis catheter into the liver graft was performed in the donor. Microdialysis samples were collected at 20-minute intervals during the donor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
65
1
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 37 publications
11
65
1
6
Order By: Relevance
“…The findings on lactate and pyruvate in study IV indicate that the microdialysate lactate/pyruvate ratio is not a good marker of ischemia during the prevailing circumstances during cold cardioplegic storage. This is supported by two other microdialysis studies of porcine cold hepatic preservation, where the lactate/pyruvate ratio did not perform well as a marker during prolonged storage (Nowak 2002, Puhl 2006.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…The findings on lactate and pyruvate in study IV indicate that the microdialysate lactate/pyruvate ratio is not a good marker of ischemia during the prevailing circumstances during cold cardioplegic storage. This is supported by two other microdialysis studies of porcine cold hepatic preservation, where the lactate/pyruvate ratio did not perform well as a marker during prolonged storage (Nowak 2002, Puhl 2006.…”
supporting
confidence: 61%
“…The G-3-P may further be hydrolyzed and recovered as glycerol (de Groot 1994). The decrease of pyruvate to undetectable levels during hours of cold storage, observed in study IV, has also been demonstrated for pig livers (Nowak 2002). The findings on lactate and pyruvate in study IV indicate that the microdialysate lactate/pyruvate ratio is not a good marker of ischemia during the prevailing circumstances during cold cardioplegic storage.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Although such technique is attractive, Gruttadauria et al 7 demonstrated that anhepatic phase without venovenous could be easily tolerated during a 30-min period, which is usually sufficient to perform the two venous sutures preceding graft revascularization. Clamping of the supracoeliac aorta produced a significant liver injury compared with the control group 4,5,6,8,13,15,16,17,18,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Microdialysis (µD), however, offers the opportunity to clinically follow various local metabolic changes in the liver for several days [16,17].…”
Section: Introductionmentioning
confidence: 99%